Collaborative Analysis of Students in Mathematics Learning in Class V of SD Negeri 1 Karanglewas - Sumito, Adib Kharisma Putra; Muslim, Arifin (Universitas Pahlawan Tuanku Tambusai, 2025)
Collaborative Analysis of Students in Mathematics Learning Class V SD Negeri 1 Karanglewas. The purpose of this study is to find out how collaborative it is between grade V students of SD Negeri 1 Karanglewas in mathematics learning. The method used in this study is a descriptive research method with a qualitative approach. With a population of 11 students in grade V of SD Negeri 1 Karanglewas, 3 students were then taken based on the level of student ability as a research sample based on the purpose sampling technique taken based on the consideration of abilities divided from 1 student with high ability, 1 student with medium ability and 1 student with low ability. The results of the study show that the collaborative nature of grade V students in mathematics learning has developed well, although there are still various aspects that require further guidance. Overall, support from teachers and principals through an active learning approach plays a role in fostering students' collaborative skills. The results of the interviews conducted were in line with previous observations.